2006
DOI: 10.1038/nsmb1141
|View full text |Cite
|
Sign up to set email alerts
|

L1 retrotransposition is suppressed by endogenously encoded small interfering RNAs in human cultured cells

Abstract: LINE-1s, or L1s, are highly abundant retrotransposons comprising 17% of the human genome. Most L1s are retrotransposition defective; nonetheless, there are approximately 100 full-length L1s potentially capable of retrotransposition in the diploid genome. L1 retrotransposition may be detrimental to the host and thus needs to be controlled. Previous studies have identified sense and antisense promoters in the 5' UTR of full-length human L1. Here we show that the resulting bidirectional transcripts can be process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
310
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(322 citation statements)
references
References 54 publications
9
310
1
2
Order By: Relevance
“…2C). This was surprising, because previous studies have suggested that Dicer-dependent siRNAs processed from long double-stranded RNA precursors are important for silencing of these elements (7,16,29). The Dicer Ϫ/Ϫ ES cells analyzed here maintain genomic DNA methylation at satellite repeats and long interspersed nuclear elements (SI Fig.…”
Section: Analysis Of Repeat-overlapping Novel Readsmentioning
confidence: 69%
“…2C). This was surprising, because previous studies have suggested that Dicer-dependent siRNAs processed from long double-stranded RNA precursors are important for silencing of these elements (7,16,29). The Dicer Ϫ/Ϫ ES cells analyzed here maintain genomic DNA methylation at satellite repeats and long interspersed nuclear elements (SI Fig.…”
Section: Analysis Of Repeat-overlapping Novel Readsmentioning
confidence: 69%
“…Then, how is TE expression activated in early preimplantation embryos? Several studies have suggested that endogenous siRNAs against TEs play an important role in TE silencing [33][34][35][36]. Despite that this endogenous siRNA silencing system is functional in zygotes [37], certain classes of TEs somehow find a way to escape this silencing system for their activation in zygotes.…”
Section: Tet3-mediated 5mc Oxidation Is Dispensable For Zygotic Gene mentioning
confidence: 99%
“…In males, this results in pachytene arrest (Bourc'his and Bestor 2004). It is also evident that small RNAs play an important role in the suppression of L1 retrotransposition in the mammalian germline (Girard et al 2006;Watanabe et al 2006;Yang and Kazazian Jr. 2006;Kuramochi-Miyagawa et al 2008). Finally the APOBEC3 family of RNA editing proteins have been shown to inhibit L1 activity in human cells (Bogerd et al 2006;Chen et al 2006;Muckenfuss et al 2006;Richardson et al 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%